Impedance spectroscopy of water splitting reactions on nanostructured metal-based catalysts. (March 2019) - Niklasson, G A; Qiu, Z; Bayrak Pehlivan, I; Edvinsson, T
Abstract: Hydrogen production by water splitting using nanomaterials as electrocatalysts is a promising route enabling replacement of fossil fuels by renewable energy sources. In particular, the development of inexpensive non-noble metal-based catalysts is necessary in order to replace currently used expensive Pt-based catalysts. We report a detailed impedance spectroscopy study of Ni-Mo and Ni-Fe based electrocatalytic materials deposited onto porous and compact substrates with different conductivities. The results were interpreted by a critical comparison with equivalent circuit models. The reaction resistance displays a strong dependence on potential and a lower substrate dependence. The impedance behaviour can also provide information on the dominating reaction mechanism. An optimized Ni-Fe based catalyst showed very promising properties for applications in water electrolysis.